Primary production assessment of the Southern Indian ocean in consumption of silicic acid - Kochergin, A.T. (Український антарктичний журнал, 2014)
Estimation of the primary productivity (PP) for the area of the Southern Indian Ocean has been made on the base of assessment of interannual variability in concentration of silicic acid in the euphotic layer. Mean for different sublatitudinal zones (subtropical, subantarctic and antarctic) summary for the vegetative period and daily PP, varied in the range 13.0-29.8 and 0.03-0.23 g C m⁻² relatively. Kerguelen Plato was the most productivity area, where summary PP reached 165 g C m⁻² and daily - 0.9. Приводятся алгоритм и результаты расчетов первичной продукции (ПП), основанные на оценке внутригодовой изменчивости содержания кремнекислоты в эвфотическом слое антарктической, субантарктической и южной границы субтропической зоны индоокеанского сектора Южного океана. Средние для этих зон значения ПП за вегетационный период и суточные изменялись в пределах 13.0-29.8 и 0.03-0.23 г С м⁻² соответственно. Наиболее продуктивным районом являлось Плато Кергелен, где суммарная ПП достигала 165 г С м⁻² и суточная – 0.9. Наводяться алгоритм і результати розрахунків первісної продукції (ПП), засновані на оцінюванні річної змінюваності вмісту кремнекислоти в евфотичному шарі антарктичної, субантарктичної та південної межі субтропічної зони індоокеанського сектора Південного океану. Середні для цих зон значення ПП за вегетаційний період та добові змінювалися в межах 13.0-29.8 і 0.03-0.23 г С м⁻² відповідно. Найбільш продуктивним районом виявилось Плато Кергелен, де сумарна ПП досягала 165 г С м⁻² та добова – 0.9.